Etude de la nature d'eau d'EL oued sur l'électrolyse - مومن بكوش, محمد خميس; دودي, طه (university of Eloued جامعة الوادي, 2018)
Hydrogen is an energy carrier that is not directly available in nature, so it must be manufactured before it is stored and used. It is essentially obtained by reforming or gasification of hydrocarbons and electrolysis of water. In this study, we experimentally studied the nature of El Oued water on the electrolysis of water. The main objective of this work is to study the electrolysis of El Oued water and to compare it with distilled water and its production of hydrogen. Consequently, the experimental study gave good results, namely the possibility of replacing the distilled water with El Oued water, while maintaining the quantity of potassium oxide. However, El Oued water alone gives very few hydrogen values in the electrolysis of water. الهيدروجين هو ناقل للطاقة غير متاح مباشرة في الطبيعة ؛ يجب أن يتم تصنيعه قبل تخزينه واستخدامه. يتم الحصول عليه أساسا عن طريق إصلاح أو تغويز الهيدروكربونات والتحليل الكهربائي للمياه. في هذه الدراسة، درسنا تجريبيا طبيعة مياه الوادي على التحليل الكهربائي. الهدف الرئيسي من هذا العمل هو دراسة التحليل الكهربائي لمياه الوادي ومقارنتها بالماء المقطر وإنتاج الهيدروجين. وبالتالي، أعطت الدراسة التجريبية نتائج جيدة، وهي إمكانية استبدال الماء المقطر بمياه الوادي، مع الحفاظ على كمية من أكسيد البوتاسيوم. ومع ذلك، تعطي مياه الوادي وحدها عدد قليل جدا من قيم الهيدروجين في التحليل الكهربائي للماء.
مذكرة ماستر في الهندسة الميكانيكة تخصص طاقوية
Keywords: Electrolysis; Hydrogen production; Oxygen production; Water of El Oued; التحليل الكهربائي; إنتاج الهيدروجين; إنتاج الأكسجين; مياه الوادي